The Effect Of Psychological Empowerment On Individual Readiness For Change With Perceived Organizational Support As A Moderator Factor: Case In Indonesian Employees Of Banking Industry - Silverius Y. Soeharso; Miskah Raihanah (AIBPM Publisher, 2023)
In Indonesia the phenomenon of organizational change occurs a lot. Many industrial sectors affected by digitalization. One of them is the banking industry.. These changes occur as a result of the industrial revolution 4.0 or often called the digital era 4.0. This study aims to determine the role of mediators of perceptions of organizational support on banking industry employees on the effect of psychological empowerment on individual readiness to change. The sample used in this study was 149 banking industry employees in particularly who worked as tellers and customer service. The findings indicated that there was a notable impact of psychological empowerment on the individual readiness to embrace change (R2 = 0.206; Sig. = 0.000). When Perceived Organizational Support is added to the moderator variable, R2 coefficient increases to become 0.258; Sig.0.000. which means that Perceived Organizational Support can moderated the relationship between psychological empowerment to individual readiness for change in Indonesia’s banking industry employees. Implication from this study, companies providing feedback related to employee performance provides employee opportunities for career development.